Polímeros impressos com íons: fundamentos, estratégias de preparo e aplicações em química analítica - Marestoni, Luiz Diego [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP]; Segatelli, Mariana Gava; Sartori, Lucas Rossi; Tarley, César Ricardo Teixeira (Sociedade Brasileira de Química, 2013)
Chemical imprinting technology has been widely used as a valuable tool in selective recognition of a given target analyte (molecule or metal ion), yielding a notable advance in the development of new analytical protocols. Since their discovery, molecularly imprinted polymers (MIPs) have been extensively studied with excellent reviews published. However, studies involving ion imprinted polymers (IIPs), in which metal ions are recognized in the presence of closely related inorganic ions, remain scarce. Thus, this review involved a survey of different synthetic approaches for preparing ion imprinted adsorbents and their application for the development of solid phase extraction methods, metal ion sensors (electrodes and optodes) and selective membranes.
Ion imprinted polymers: fundamentals, preparation strategies and applications in analytical chemistry
Keywords: imprinting technology; preconcentration; sensors